Expression and Mutagenesis studies of Candida antactica lipase B - Rotticci-Mulder, Johanna C. (KTH, Bioteknologi, 2003)
Recombinant Candida antarctica lipase B was successfullyproduced in the methylotropic yeast Pichia pastoris. Thespecific activities of Candida antarctica lipase B produced inPichia pastoris and commercial Candida antarctica lipase B fromNovozymes were the same. In shake-flask cultivations theexpression levels were about 25 mg L-1. Production levels couldbe increased to 1.5 g L-1, using a fermentor. A model tosimulate growth and oxygen consumption was described. The highcell density growth could be explained by the low maintenancecoefficient of Pichia pastoris. Enrichment of the aeration withoxygen increased the recombinant protein production. The lipasewas also produced as a fusion to a cellulose binding module.The cellulose binding module did not interfere with thespecific activity of the lipase. With this fusion proteincatalytic reactions can be performed in close proximity to acellulose surface. The binding module can also function as anaffinity tag for purification. Establishment of the Candidaantarctica lipase B production system allowed the engineeringof Candida antarctica lipase B variants. Four differentvariants were produced in order to investigate if electrostaticinteractions contributed to enantioselectivity. Theenantioselectivity of two halogenated secondary alcohols wasdoubled for the Ser47Ala variant. Thisimplied thatelectrostatic interactions are important forenantioselectivity. The Trp104His variant showed a decrease inenantioselectivity for all tested substrates. This was causedby an increase in the size of the stereoselectivity pocket.Symmetrical secondary alcohols of different size were used tomap the stereoselectivity pocket. A substituent as large as apropyl or isopropyl could be accommodated in the pocket of theTrp104His variant. In the wild-type lipase thestereoselectivity pocket was estimated to fit an ethyl group.The enzyme variants were subjected to a thermodynamic study, toelucidate changes in the enthalpic and entropic contributionsto enantioselectivity. The enthalpic and entropic ...